Thermal cyclic behavior and lifetime prediction of self-healing thermal barrier coatings. (July 2021) - Krishnasamy, Jayaprakash; Ponnusami, Sathiskumar A.; Turteltaub, Sergio; van der Zwaag, Sybrand
Highlights: Cyclic thermomechanical lifetime simulations of self-healing thermal barrier coatings. Microscale modelling with crack healing, TGO growth and crack tracking algorithm. Crack growth rate decreases with increasing crack filling ratio and healing strength. Presence of inactive healing particles may be detrimental to TBC performance. Near linear TBC lifetime extension with increasing healing fracture properties. Abstract: The thermal cyclic behavior of self-healing thermal barrier coatings (SH-TBC) is analyzed numerically to develop a lifetime prediction model. Representative microstructures are studied adopting a unit cell based multiscale modeling approach along with a simplified evolution model for the thermally-grown oxide layer (TGO) to study the evolution of damage and healing in a self-healing TBC system. The fracture and healing process is modeled using the cohesive zone-based healing model along with a crack tracking algorithm. The microstructural model includes splat boundaries and a wavy interface between the Top Coat and the Bond Coat, typical of Air Plasma Sprayed TBCs. A particle-based self-healing mechanism is accounted for with a random distribution of healing particles subjected to a numerically accelerated thermal cyclic loading condition. Lifetime extension of the self healing TBCs is quantified by conducting thermal cyclic analyses on conventional TBCs (benchmark system without self-healing particles). Parametric analyses on healing parameters such as crack filling ratio and strength recovery of the healed crack are also conducted. The results are presented in terms of the evolution of the crack pattern and the number of cycles to failure. For self-healing TBCs with a suitable healing reaction (i.e., cracks being partially filled and a minimal local strength after healing), an improvement in TBC lifetime is observed. In contrast, if the healing mechanism is not activated, the presence of the healing particles is actually detrimental to the lifetime of the TBC. Correspondingly, in addition to superior crack filling ratio and healed strength, significant improvement in lifetime is achieved for self healing TBCs with a higher probability of crack-healing particle interaction. This highlights the importance of a robust activation mechanism and a set of key material requirements in order to achieve successful self-healing of the TBC system.